Evolving Paradigms in Gynaecological Practices: From Clinical Judgment to Technological Precision - Amey Chugh; Madhura Deshmukh (Journal of Clinical and Diagnostic Research)
Over the past few decades, the landscape of gynaecological practice has changed significantly, reflecting advances in medical technology, societal views, and patient demographics [1]. Historically, gynaecology largely relied on subjective evaluations and clinical judgment. With limited means of investigations, diagnoses and treatments were frequently made only on the basis of personal experience and physical examinations. In contrast, advances in technology are driving gynaecological practice today.